2013
DOI: 10.1073/pnas.1308243110
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing in patients with retinitis pigmentosa reveals pathogenic DNA structural changes and NEK2 as a new disease gene

Abstract: We performed whole genome sequencing in 16 unrelated patients with autosomal recessive retinitis pigmentosa (ARRP), a disease characterized by progressive retinal degeneration and caused by mutations in over 50 genes, in search of pathogenic DNA variants. Eight patients were from North America, whereas eight were Japanese, a population for which ARRP seems to have different genetic drivers. Using a specific workflow, we assessed both the coding and noncoding regions of the human genome, including the evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 33 publications
2
72
0
Order By: Relevance
“…Whole-genome sequencing will offer a more suitable detection technique for these mutation mechanisms. 38 In conclusion, our study emphasized that IBD-guided mutation analysis and/or WES is a powerful tool for the molecular diagnosis of RD-even in a single individual. We unmasked unusual molecular and consequent clinical findings-the latter guiding future medical management and prognosis.…”
Section: Discussionmentioning
confidence: 69%
“…Whole-genome sequencing will offer a more suitable detection technique for these mutation mechanisms. 38 In conclusion, our study emphasized that IBD-guided mutation analysis and/or WES is a powerful tool for the molecular diagnosis of RD-even in a single individual. We unmasked unusual molecular and consequent clinical findings-the latter guiding future medical management and prognosis.…”
Section: Discussionmentioning
confidence: 69%
“…Our small cohort size is a potential limitation, though the sample size is comparable to other recent disease-cohort based WGS studies and is reflective of the prospective study design. 15,16 Our study is however the first WGS study in any nephrology cohort.…”
Section: Discussionmentioning
confidence: 96%
“…This affords broad power to detect single-nucleotide variants (SNVs) and small insertions and deletions (indels), and the ability to detect larger copy number variants (CNVs) and structural variants (SVs), such as inversions and translocations. 15,16 Since the introduction of the Illumina HiSeq X sequencing system, the cost of WGS has decreased significantly and is likely to continue to reduce in cost over time.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, given the extreme genetic heterogeneity of RP, numerous disease-related mutations have been discovered by TES or WES. 3,8 However, almost all current reports focus on single-nucleotide polymorphisms or insertions/deletions detected by NGS, thereby discarding information in uncovered or low-depth regions. Several previous studies of RP briefly reported this phenomenon without detailed investigation or deep discussion.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 WGS analyzes the entire genome and is especially useful for detecting mutations in noncoding regions, structural variations, and copy-number variations. 8 Both TES and WES are commonly used to detect pathogenic mutations in patients with RP; WGS is less widely used than TES or WES, primarily because of its high cost. Although numerous diseasecausing genes and mutations in RP have recently been identified by TES and WES, a considerable proportion of RP cases seem to lack these pathogenic mutations.…”
Section: Introductionmentioning
confidence: 99%